2017
DOI: 10.3389/fphar.2016.00533
|View full text |Cite
|
Sign up to set email alerts
|

Exosome-Based Cancer Therapy: Implication for Targeting Cancer Stem Cells

Abstract: Drug resistance, difficulty in specific targeting and self-renewal properties of cancer stem cells (CSCs) all contribute to cancer treatment failure and relapse. CSCs have been suggested as both the seeds of the primary cancer, and the roots of chemo- and radio-therapy resistance. The ability to precisely deliver drugs to target CSCs is an urgent need for cancer therapy, with nanotechnology-based drug delivery system being one of the most promising tools to achieve this in the clinic. Exosomes are cell-derived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
137
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(148 citation statements)
references
References 115 publications
0
137
0
Order By: Relevance
“…Biomimetic nanomaterials have been extensively studied as drug delivery vectors, such as exosomes . Exosomes are a type of micro vesicle secreted by cells, which can transfer internal substances to surrounding cells efficiently through rich adhesion proteins interacting with cell membrane . Based on the above, we selected HFL‐1 cells as the maternal cells for the source of exosomes, which were characterized by DLS and TEM; the results showed that the average particle size was 88.45 ± 19.53 nm, with uniform size and typical vesicular structure.…”
Section: Discussionmentioning
confidence: 99%
“…Biomimetic nanomaterials have been extensively studied as drug delivery vectors, such as exosomes . Exosomes are a type of micro vesicle secreted by cells, which can transfer internal substances to surrounding cells efficiently through rich adhesion proteins interacting with cell membrane . Based on the above, we selected HFL‐1 cells as the maternal cells for the source of exosomes, which were characterized by DLS and TEM; the results showed that the average particle size was 88.45 ± 19.53 nm, with uniform size and typical vesicular structure.…”
Section: Discussionmentioning
confidence: 99%
“…Besides anti‐cancer therapeutic drugs, exosomes can also deliver various tumour antigens. Thus, exosomes could present CSC‐specific antigens to T cells and activate T cells for anti‐CSC immunization . In addition, exosomes can be used as natural nanovesicles to deliver exogenous small RNAs, including siRNA and microRNAs, which target CSC‐specific signal pathways, such as Wnt, Notch, Hippo, and Hedgehog, etc.…”
Section: Exosomes As Drug‐delivery Vehicles For Targeted Cancer Therapymentioning
confidence: 99%
“…The advantage in size enables better biodistribution and bioavailability of exosomes in the human body. Escape of lung clearance and permeability across the blood-brain barrier were reported for exosome-based drug carriers (200, 254). In addition, exosomes could achieve targeted delivery compared to synthetic nanoparticles.…”
Section: Translational Applications Of Evs In Cancermentioning
confidence: 87%
“…Cancer cells secrete more EVs than normal cells (193, 194), and consequently, patients with cancer have higher levels of EVs compared to healthy individuals (195200). With the increased level of EVs in circulation and the packaging of cancer-related molecules, these vesicles may serve as promising biomarkers for cancer diagnoses.…”
Section: Translational Applications Of Evs In Cancermentioning
confidence: 99%